2015
DOI: 10.1210/en.2015-1308
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Bone and Wnt10b Expression in Male Type 1 Diabetic Mice Is Blocked by the Probiotic Lactobacillus reuteri

Abstract: Type 1 diabetes (T1D)-induced osteoporosis is characterized by a predominant suppression of osteoblast number and activity, as well as increased bone marrow adiposity but no change in osteoclast activity. The fundamental mechanisms and alternative anabolic treatments (with few side effects) for T1D bone loss remain undetermined. Recent studies by our laboratory and others indicate that probiotics can benefit bone health. Here, we demonstrate that Lactobacillus reuteri, a probiotic with anti-inflammatory and bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
137
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(149 citation statements)
references
References 74 publications
8
137
0
Order By: Relevance
“…33 In another study, the addition of L. reuteri prevented TNF-α-mediated suppression of Wnt10b and osteoblast maturation markers in type 1 diabetes (T1D)-induced osteoporosis. 34 In this study, we showed that probiotic treatment protected mice from wear debris-induced osteolysis. Treatment with L. casei ameliorated CoPs-induced bone loss and osteoclast formation.…”
mentioning
confidence: 67%
“…33 In another study, the addition of L. reuteri prevented TNF-α-mediated suppression of Wnt10b and osteoblast maturation markers in type 1 diabetes (T1D)-induced osteoporosis. 34 In this study, we showed that probiotic treatment protected mice from wear debris-induced osteolysis. Treatment with L. casei ameliorated CoPs-induced bone loss and osteoclast formation.…”
mentioning
confidence: 67%
“…Consistent with this, Sjogren et al found that bacterial colonization of young adult GF animals resulted in loss of trabecular bone mass and an increase in bone-resorbing osteoclasts (13). However, other studies have suggested that treatment with beneficial microbes modestly increases bone mineral density (21)(22)(23)(24)(25)(26) and protects against bone loss after sex steroid deficiency (27). Discrepant results in studies examining the effect of microbiota on bone may reflect differences in the composition of the resident microbiota, age of the animal at colonization and necropsy, mouse strain, and sex.…”
mentioning
confidence: 87%
“…The probiotic Lactobacillus reuteri has anti-TNFα properties, reduces gut inflammation, and strengthens gut barrier function in vitro [104][134][147]. When given to mice, L. reuteri treatment was found to increase bone density in healthy male mice in addition to preventing bone loss in both female ovariectomized mice and type 1 diabetic male mice[134][104, 148][149]. Taken together, these data demonstrate the role of the microbiome and intestine in maintaining bone density.…”
Section: Barrier Pathophysiology In Diseasementioning
confidence: 99%
“…Intestinal health has been shown to play a key role in the development of T1D [163165]. Additionally, T1D induced changes in intestinal health and function have been suggested to contribute to further T1D complications, such as osteoporosis [166]. Intestinal changes that have been reported to precede or be caused by T1D which can influence bone health include intestinal barrier function or permeability and the intestinal microbiota [167174].…”
Section: Barrier Pathophysiology In Diseasementioning
confidence: 99%
See 1 more Smart Citation